Ionophoretic Study of Complexation Reactions of Mixed Ligand Complexes in Copper(II), Nickel(II), Zinc(II) and Cobalt(II)-Nitrilo-tri-Acetate-Benzoate Systems - Panda, C.S.; Trivedy, R.S.; Sinha, C.K.; Kumari, Neelam (Asian Journal of Chemistry, 2010)
Paper-electrophoresis is adopted for the study of the equilibria in mixed ligand complex system in solution. Here in addition to a constant concentration of a primary ligand, the background electrolyte (0. 1M HNO3) also contains nitrilo-tri-acetic acid (NTA) as a secondary ligand at fixed pH 8.5. The increasing amount of NTA is added to the background electrolyte and the movement of spot of the metal ions are measured under an influence of electric field. The graphs were plotted in log [benzoic acid] versus mobility, which furnish information of the formation of mixed ligand complex and to calculate its stability constant. The metal(II)-benzoate and metal(II)-nitrilo-tri-acetate binary systems have also been studied since they are a pre-requisite for the study of mixed ligand complexes.